A framework for assessing freshwater vulnerability along China's Belt and Road Initiative: An exposure, sensitivity and adaptive capacity approach. Issue 132 (June 2022) - Battamo, Ashenafi Yohannes; Varis, Olli; Giesy, John P.; Oba, Belay Tafa; Aborisade, Moses Akintayo; Sun, Peizhe; Yang, Yongkui; Zhao, Lin
Abstract: In the Belt and Road Initiative (BRI) countries, freshwater systems are sensitive and prone to natural variability, human interventions and climate change. Yet, freshwater vulnerability has not been quantified at the BRI scale. The primary goal of this study was to identify and quantify the most vulnerable BRI regions and explain reasons for identified vulnerability. The assessment was based on the conceptual framework recommended by the Intergovernmental Panel on Climate Change (IPCC), which considers three components of vulnerability including exposure, sensitivity and adaptive capacity. Twenty-four key indicators were selected and the TOPSIS-entropy-weight algorithm was used to calculate weights and ranks of each component that were then used to rank 123 BRI countries based on their closeness coefficient. The results indicate that 69% of them were categorized as having medium to highest freshwater vulnerability. Of these, countries in developing regions, particularly those in Sub-Saharan Africa and in the stretch from South Asia to the Mediterranean, were among the highest vulnerable. The analysis revealed that root causes for the highest vulnerability differ among regions. In Sub-Saharan Africa, low adaptive capacity was the primary reason for this, while high sensitivity was the predominant cause in the most vulnerable stretch of Asia. These findings highlight the importance of developing context-specific policies to improve adaption capacity in Sub-Saharan Africa and to decrease sensitivity in vulnerable parts of Asia. Therefore, to address hazards associated with the highest level of vulnerability, BRI investments should combine adequate water-efficient physical infrastructures with fostering economic performance and institutional capacities. Highlights: A country-level framework to assess freshwater vulnerability was developed for BRI countries. Countries in Sub-Saharan Africa exhibited the highest vulnerability, mainly due to the lowest adaptive capacity. Vulnerability of South, Central and West Asia was due to those countries having the highest sensitivity. Greater capacity to adapt is particularly critical in the most vulnerable countries.